University’s Official Instagram as a News Sources for The Media - Utami, Nadia Wasta; Prastya, Narayana Mahendra (Jurnal Komunikasi dan Bisnis, 2024)
Media relations play a crucial role in the public relations activities of universities, as they provide opportunities for increased media exposure. In today's journalism landscape, social media has become a prominent source of news for journalists. This includes official university accounts, which serve as valuable sources of information for journalists. Consequently, university public relations must understand the perspective of journalists when selecting and disseminating information through social media platforms. This article aims to explore how journalists utilize information from university social media accounts, specifically Instagram, as news sources. The concept of information subsidies is used to analyze the public relations activities involved in providing journalists with access to information and ensuring its quality. The research adopts a qualitative approach, utilizing interviews with journalists from the education sections of kompas.com and detik.com. The findings of this research highlight despite the prevalence of visual content, limited text, and informal language often used by university Instagram users, journalists still find value in quoting from Instagram. This suggests that the information available on social media platforms is sufficient to fulfill journalists' informational needs. Journalists also rely on university Instagram accounts as a source of news. The significance of higher education institutions acknowledging social media as a platform for distributing information to journalists. The prevalent topics covered in news articles include advice, contemporary matters, and education sector-related information. The majority of cited news items are derived from expert opinions or contributions from university lecturers. It is crucial to establish efficient strategies for social media management in order to accentuate various themes or content that showcase the expertise of university staff.